2014
DOI: 10.2147/ppa.s64825
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence behaviors of Medicare beneficiaries

Abstract: BackgroundMedication adherence is crucial for positive outcomes in the management of chronic conditions. Comprehensive medication consultation can improve medication adherence by addressing intentional and unintentional nonadherence. The Medicare Part D prescription drug benefit has eliminated some cost barriers. We sought to examine variables that impact self-reported medication adherence behaviors in an ambulatory Medicare-beneficiary population and to identify the factors that influence what information is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Our meta-analysis was based on systematic collected studies relating to TLR4 gene polymorphisms and glaucoma. To our knowledge, this is the first study that attempted to combine the POAG and NTG studies because these two types of glaucoma are overlapping in some factors [5,6]. Interestingly, combined analysis showed rs1927911, rs12377632, and rs2149356 in the allele contrast model were strongly associated with glaucoma (POAG and NTG) suggesting that the POAG and NTG share some pathogenesis factors that may relate to TLR4.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our meta-analysis was based on systematic collected studies relating to TLR4 gene polymorphisms and glaucoma. To our knowledge, this is the first study that attempted to combine the POAG and NTG studies because these two types of glaucoma are overlapping in some factors [5,6]. Interestingly, combined analysis showed rs1927911, rs12377632, and rs2149356 in the allele contrast model were strongly associated with glaucoma (POAG and NTG) suggesting that the POAG and NTG share some pathogenesis factors that may relate to TLR4.…”
Section: Discussionmentioning
confidence: 89%
“…POAG and NTG share similarities in phenotypes composed of having normal anterior chamber angles, peripapillary retinal nerve fiber layer (RNFL) thinning, glaucomatous optic neuropathy (GON), and corresponding visual field (VF) defects. Therefore, it is believed that POAG and NTG illustrate a continuum of open-angle glaucoma in which there is a difference in some causative factors and IOP [5,6]. Although the precise and accurate molecular mechanisms of POAG and NTG have not been investigated, it is possible that patients with POAG and NTG have some overlapping factors in both multiple genetic and environmental interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Difficulty paying for care, such as prescription medications, may be a barrier for patients [5]. Using a single-item measure, participants were asked to describe their household’s current financial situation [16].…”
Section: Methodsmentioning
confidence: 99%
“…These factors include having low health literacy, being of lower socioeconomic status, and experiencing barriers such as forgetfulness [59]. While these are real and often tangible barriers, underlying these factors – and the ability to overcome them – are health beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Individual factors such as socioeconomic status, age, sex, race, and mental status and health system factors such as health literacy, convenience of pharmacy, and the complexity of the medication regimens all contribute to medication adherence by chronically diseased patients. 4 , 5 Looking at patients with geriatric depression, human immunodeficiency virus, diabetes mellitus, and hypertension, Libby et al used the Medication Regimen Complexity Index to evaluate medication adherence. They found that dosing frequency and the variety of dosage forms were important components of medication complexity.…”
Section: Effect Of Dosing Frequency On Medication Adherence In Chronimentioning
confidence: 99%